Assessing the Utility of Compound Trait Estimates of Narrow Personality Traits. Issue 5 (2nd September 2016) - Credé, Marcus; Harms, Peter D.; Blacksmith, Nikki; Wood, Dustin
ABSTRACT: It has been argued that approximations of narrow traits can be made through linear combinations of broad traits such as the Big Five personality traits. Indeed, Hough and Ones (2001 ) used a qualitative analysis of scale content to arrive at a taxonomy of how Big Five traits might be combined to approximate various narrow traits. However, the utility of such compound trait approximations has yet to be established beyond specific cases such as integrity and customer service orientation. Using data from the Eugene-Springfield Community Sample (Goldberg, 2008 ), we explore the ability of linear composites of scores on Big Five traits to approximate scores on 127 narrow trait measures from 5 well-known non-Big-Five omnibus measures of personality. Our findings indicate that individuals' standing on more than 30 narrow traits can be well estimated from 3 different types of linear composites of scores on Big Five traits without a substantial sacrifice in criterion validity. We discuss theoretical accounts for why such relationships exist as well as the theoretical and practical implications of these findings for researchers and practitioners.